Integrated Bioinformatics Analysis Identifies ELAVL1 and APP as Candidate Crucial Genes for Crohn's Disease. (17th July 2020) - Li, Heli; Li, Qianru; Sun, Shiran; Lei, Ping; Cai, Xiong; Shen, Guanxin
Abstract : Immune imbalance and barrier destruction of intestinal mucosa are the central pathogenic factors of Crohn's disease (CD). In this study, three independent microarray studies of CD were integrated and 9912 differentially expressed genes (DEGs) were analysed by NetworkAnalyst to screen candidate crucial genes. NetworkAnalyst identified ELAV-like RNA binding protein 1 (ELAVL1) as the most crucial upregulated gene and amyloid- β precursor protein (APP) as the most crucial downregulated gene in peripheral blood of CD patients. By computing significance with hypergeometric test based on the KEGG pathway database, upregulated DEGs highlight the pathways of T cell receptor signaling and the differentiation of T helpers. Downregulated DEGs were found enriched in pathways in multiple cancers, MAPK signaling, Rap1 signaling, and PI3K-AKT signaling. Further taking all DEGs together, Gene Set Enrichment Analysis (GSEA) brought out the NOD-like receptor (NLR) signaling pathway which could be regulated by ELAVL1. xCell found decreased naïve and differentiated T cell proportions in the peripheral blood of CD patients suggesting T cell migration to the intestinal tissue and/or exhaustion. Further, ELAVL1 expression correlating with multiple T cell proportions suggests that ELAVL1 may regulate T cell activation. These findings illustrated that ELAVL1 and APP were candidate crucial genes in the peripheral blood of CD patients. ELAVL1 possibly acts as a key regulator of T cell activation via the NLR signaling pathway. APP might be a downstream effector of infliximab treatment connecting with MAPK signaling.